2020
DOI: 10.1021/acsomega.9b03358
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of Structure–Activity Relationship between Structure and Tribological Properties of Bulk Layered Materials by Four-Ball Friction Tester

Abstract: Encouragingly, a lot of research studies have demonstrated that two-dimensional (2D) nanosheets applied as an additive in oils show preferable friction-reducing and wear resistance performance. However, the current issue was that an elusive way could be adopted to probe the structure–activity relationship between the structure and tribological properties of bulk layered materials due to the structural evolution during friction testing. In this study, we studied the structure–activity relationship between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is found that the optimal addition of Ag NWs/2D Ni-BDC in oil lies at 0.04 wt %, wherein the friction coefficient and wear scar diameter both have the lowest value. The excessive addition of content will lead to the occurrence of adhesive wear, attributed to the aggregation of Ag NWs/2D Ni-BDC between friction pairs. , Figure b shows the typical friction curves of the friction coefficient of three comparative samples depending on the running time at 0.04 wt %. Obviously, the friction coefficient of Ag NWs/2D Ni-BDC is throughout more stable and lower than the other two samples, decreasing by 38% (pure base oil) and 17% (2D Ni-BDC) in the friction coefficient and by 37% (pure base oil) and 12% (pure base oil) in the wear scar diameter (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the optimal addition of Ag NWs/2D Ni-BDC in oil lies at 0.04 wt %, wherein the friction coefficient and wear scar diameter both have the lowest value. The excessive addition of content will lead to the occurrence of adhesive wear, attributed to the aggregation of Ag NWs/2D Ni-BDC between friction pairs. , Figure b shows the typical friction curves of the friction coefficient of three comparative samples depending on the running time at 0.04 wt %. Obviously, the friction coefficient of Ag NWs/2D Ni-BDC is throughout more stable and lower than the other two samples, decreasing by 38% (pure base oil) and 17% (2D Ni-BDC) in the friction coefficient and by 37% (pure base oil) and 12% (pure base oil) in the wear scar diameter (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is unable to demonstrate desirable properties such as a large specific area effect, volume impact or quantum size effect. So, surface modification must be performed to increase the compatibility of TiO 2 with organic systems and its dispersion stability in organic systems, as well as the overall performance of the composite system including TiO 2 NPs (Wang et al, 2022b;Kong et al, 2019Kong et al, , 2020Yao et al, 2005;Li and Zhu, 2003).…”
Section: Introductionmentioning
confidence: 99%